Association Between Serial B‐Type Natriuretic Peptide Levels, Vasoactive Drug Weaning, and Adverse Cardiovascular Outcomes in Pediatric Heart Failure - Karla L. Loss; Jennifer Su; JonDavid Menteer; Molly A. Weisert; Robert E. Shaddy; Paul F. Kantor (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Children hospitalized with acute decompensated heart failure (ADHF) frequently require intravenous vasoactive (IVV) support drugs and are at risk for adverse cardiovascular (ACV) outcomes. We wished to assess whether serial changes in B‐type natriuretic peptide (BNP) levels are associated with successful weaning off IVV support and/or prespecified ACV outcomes in children hospitalized with ADHF. Methods and Results Children hospitalized with ADHF from 2005 to 2021 at our institution were assessed for serial changes in BNP, weaning off of IVV support, and ACV outcomes. Changes in BNP level were evaluated using linear mixed‐effects modeling. Bonferroni correction was used to adjust for multiple hypothesis testing. In 131 hospitalizations of children with ADHF, the median age was 4.8 years, with 74% receiving IVV support. ACV outcomes occurred in 62 children. IVV support was associated with lower admission left ventricular ejection fraction (26.7% versus 32%, P=0.002), more severe left ventricular dilation (left ventricular internal diastolic dimension Z score 5.9 versus 3.1, P=0.021) moderate or more mitral regurgitation (41.3% versus 20.6%, P=0.038), and qualitative right ventricular systolic dysfunction (in 45.4% versus 11.8%, P<0.001). Decline in BNP levels was more rapid in patients who were successfully weaned from IVV support (−0.20 versus –0.03 2log pg/mL per day, P<0.001) and in the non‐ACV group (−0.17 versus –0.03 2log pg/mL per day, P<0.001). Right ventricular systolic dysfunction was an independent risk factor for ACV (odds ratio, 2.49; P=0.045). Conclusions The declining rate of serial BNP levels was associated with weaning from IVV support and no ACV outcomes in children hospitalized with ADHF. Right ventricular systolic dysfunction was associated with ACV outcomes.